CORROSION PROTECTION THROUGH THE USE OF INHIBITORS - Pizarro Cabrera, Raúl (2006)
The problem of the metallic corrosion constitutes a fundamental aspect in the present society, which rests in the employment of metallic material in a proportion never used up to now. From among the diverse procedures that are employed to avoid this metallic deterioration, the corrosion inhibitions constitute one of the more etfeclive methods and inexpensive lor ihe protection of metals front the aggressive attack of the environment where they are utilized. Thus, an adequate use of the inhibiters may multiply for ten the lile of the equipment in service, to prevent accidents and, ín sorne cases, to permit the utilization of steels and ordinary alloys instead ol other sophisticated materials and, expensive.